Rectal Prolapse in 12 Patients Treated by Posterior Prolene Mesh Rectopexy and Sigmoid Colon Resection - Perek, Asiye; Soylu Yalıman, Selen; Yurdanur Kılıç, Hazal; Özcan, Pırıltı; Süphan Ertürk, Murat; Vedat Durgun, Ali (Cerrahpaşa Medical Journal, 2025)
Objective: The aim of this study was to evaluate morbidity, mortality, postoperative function, and recurrence in patients treated by posterior prolene mesh rectopexy and sigmoid colon resection for complete rectal prolapse (CRP), focusing on postoperative patient satisfaction, recurrence, and functional outcomes. Methods: In this retrospective study, we evaluated the outcomes of 12 patients treated with posterior prolene mesh rectopexy and sigmoid colon resection between 2018 and 2022. Perioperative data were noted. At follow-up, functional results, patient satisfaction and recurrence were determined. Twelve patients were assessed at a median interval of 32 months. Results: None of the patients developed intraabdominal infections. One patient had postoperative pulmonary emboli, which resolved with medical therapy expressed constipation. All of the patients expressed full satisfaction with the result of the operation in the follow-up period, with a median time of 32 months. Two patients had anterior mucosal prolapsus about 1 cm in forceful straining, 1 patient had gas incontinence from time to time Conclusion: Sigmoid resection with posterior prolene mesh rectopexy appears to be a safe procedure in controlling CRP. Cite this article as: Perek A, Soylu Yalıman S, Yurdanur Kılıç H, Özcan P, Ertürk MS, Durgun AV. Rectal prolapse in 12 patients treated by posterior prolene mesh rectopexy and sigmoid colon resection. Cerrahpaşa Med J. 2025; 49, 0020, doi: 10.5152/cjm.2025.24020.